Faktor Yang Mempengaruhi Minat Beli Paket Internet XL Axiata di Kota Palembang - Suherman, Kenrick; Artina, Nyimas (MDP Student Conference, 2024)
This research aims to examine the influence of product quality,and price on interest in purchasing XL Axiata internet packages in the city of Palembang, both partially and simultaneously. The technique used for data collection was by distributing questionnaires on a Likert scale, with a total of 230 respondents. The type of research used in this research is a quantitative approach. The sampling technique uses non-probability sampling. Data processing in this research was assisted by SPSS 25 software. The results of this research show that partially product quality (X1), and price (X2), have a positive and significant influence on buying interest. This research simultaneously shows that all independent variables used in the research, namely product quality (X1), and price (X2) have an influence on purchasing interest.